HISTORICAL DYNAMICS MADRASAH MUALLIMIN UNIVA MEDAN (1958-2018) - Ihyaur Rahmi, Hasan Asari, Ja’far (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This research aims to describe the historical dynamics Madrasah Muallimin UNIVA Medansince 1958 to 2018. This research use historical research, which is conducted four steps; 1). heuristics, 2).criticism, 3). interpretation, and 4). historiography. The sample of this research was the headmaster ofmadrasah, teachers, alumni, and the references which is related to research. The result of this study waswritten in three chapters; chapter II: The background of the establishment of Madrasah Muallimin UNIVAMedan which is seen from 3 aspects; a) Intellectual background: the establishment of Madrasah Mualliminwas to prepare students of Universitas of Al Washliyah (UNIVA) Medan and to prepare religion teacher; b)Religious background; the : the establishment of Madrasah Muallimin is to prepare Al Jam’iyatul Washliyah’sfuture Ulama; c) Social background of Madrasah Mualimin caused by high public interest to continue theireducation to Aliyah and Higher Education levels while at that time Aliyah’s institutions were limited.Chapter III: Historical dynamic Madrasah viewed from 3 aspect, a) Curriculum: Madrasah MualliminUNIVA Medan implemented in two curricula namely Al Jam’iyatul Washliyah curriculum and Nationalcurriculum from the beginning until now; b) Educator: educators in Madrasah Muallimin are profesionaleducator both educators for diniyah lessons and general lessons educators with traditions Madrasah ofrecruited especially for diniyah lesson educators with a lifetime of service or as long as the educator is ableto educate at Madrasah Muallimin UNIVA Medan; c) Students: The students of madrasah Muallimincomes from various regions in Indonesia, especially North Sumatera and some them comes from Malaysiawith the number of studets constantly increasing. Chapter IV: The historical dynamcs of social relevanceof madrasah while maintainng the characteristics of the learning by traditional Islamic texts andmadrsah program innovations in the form of Tahfiz progrmas and Alquran clinical programs.Keyword: Dynamics, Historrycal and Madrasah